Mechanically strong, stretchable and self-healable silicone elastomers with designed dynamic networks for exceptional self-adhesion under harsh conditions - Shuai-Chi Liu; Yu-Tong Li; Yu-Qing Qin; Ling Yang; Meng-Ying Liu; Ji Liu; Yang Li; Cheng-Fei Cao; Li-Xiu Gong; Shi-Neng Li; Guo-Dong Zhang; Long-Cheng Tang (Advanced Industrial and Engineering Polymer Research, 2025)
Silicone elastomers with wide-temperature stability and excellent mechanical flexibility have attracted considerable interest in both academic and industrial fields. However, the highly cross-linked networks cannot self-heal and usually show poor adhesion to other substrates, limiting their sustainable applications in emerging fields. Developing self-adhesive organosilicon elastomers with high mechanical strength, superior stretchability, and exceptional self-healing performance remains a significant challenge. Herein, we propose a facile method to synthesize self-adhesive organosilicon elastomers with high mechanical strength, flexibility, and self-healing performance by designing dynamic networks. Specifically, multiple reversible physical and chemical bonds, such as disulfide bonds, hydrogen bonds, and Zn2+ coordination bonds, are integrated into the organosilicon chains via click reactions, carboxylic acid-amine condensation, and ionic coordination. The optimized organosilicon elastomers exhibit exceptional stretchability and mechanical properties, including an elongation at break of ∼5600 %, high strength (2.2 MPa), and toughness (54.38 MJ/m3), outperforming traditional organosilicon elastomers. Additionally, the as-prepared elastomers demonstrate remarkable self-healing ability, with 80–93 % healing efficiency at 25–60 oC, and excellent self-adhesion to various substrates (0.3–1.0 MPa on aluminum, steel, and wood). These properties are maintained under harsh conditions, including low temperature (−10 oC), saltwater, and organic solvents. Clearly, the organosilicon elastomers developed in this work hold significant potential as green and sustainable candidates for various self-adhesive applications.